A collaborative-affirmative approach to supervisory practice - Baptist, Joyce A.; Aducci, C. J. (My University, 2012)
As gatekeepers of the profession, supervisors must work to ensure that supervisees do no harm to their clients. At times this requires a more hierarchical approach to supervision, which may pose difficulties for supervisors working from a collaborative stance. These matters may become intensified when supervisees work with LGB clients and affirmative supervision becomes necessary, which tends to come from a “knowing” stance. By highlighting the aspects of collaborative and affirmative supervision and the necessity of affirmative supervision, this paper provides an affirmative approach to supervision that is congruent with collaborative supervisory practices. A way of including the presence of the LGB client in supervision in an effort to merge collaborative and affirmative supervision is addressed. An overview of the collaborative-affirmative approach, as well as supervisees who may be suitable candidates for receiving collaborative-affirmative supervision is discussed. The implications of the approach and its possible limitations are provided.
Keywords: Supervision; Collaborative supervision; Affirmative supervision; Collaborative-affirmative supervision